Diamond frenotomy: A novel surgical technique for gummy smile aesthetic correction - Shalahuddin Maulidi; Evi Urwatul Wusqo; Nida Hana Salsabila; Agung Krismariono (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2026)
Background: A ‘gummy’ smile, also known as excessive gingival display, is a dental condition characterized by the excessive visibility of the gums when a person smiles. This condition typically occurs when more than 3–4 mm of gum tissue is exposed, making the teeth appear shorter and affecting the smile’s aesthetic appeal. Purpose: This case report aims to explain the minimally invasive surgery technique for correcting a gummy smile using diamond frenotomy. Case: A 24-year-old woman with the chief complaint that her gingiva was visible excessively when smiling. Case management: Intraoral examination on the maxillary anterior region showed a gingival margin at the normal position, normal texture, standard color of gingiva, and normal crown size. Diamond frenotomy with a double mosquito hemostat was inserted parallel to the attached gingiva and vestibule, then incised until the two mosquito clamps met, producing the remaining frenum tissue to be excised. Following evaluation over six months, the gummy smile was observed to have been significantly reduced. Conclusion: Diamond frenotomy is an innovative surgical technique for gummy smile correction.